Іншоєпархіальні студенти у Волинській духовній семінарії (1945–1964 рр.) - Федчук, Олександр; Fedchuk, Oleksandr (My University, 2015)
У статті проаналізовано територіальне походження студентів Волинської духовної семінарії. З’ясовано, скільки з них були вихідцями з-поза меж Волинсько-Рівненської єпархії. Установлено час появи в семінарії перших таких студентів. Виявлено єпархії, із яких прибувала до навчального закладу найбільша кількість абітурієнтів.In the article analyzed the territorial origin of students of the Volyn theological Seminary. Ascertained the time of existence of the regional principle of the training of clergy in this educational establishment, and also the coming of the first students from the dioceses for which the Seminary was not required to train personnel at this time. Established how many seminarians did not come from the Volyn- Rivne diocese. Found out the dioceses, of which arrived to the educational establishment the largest number of applicants.
Students of Others Dioces in the Volyn Theological Seminary (1945-1964.)
Keywords: Волинська духовна семінарія; Волинсько-Рівненська єпархія; Мукачівська єпархія; семінаристи; Volyn theological Seminary; Volyn-Rivne diocese; Lviv-Ternopil diocese; Mukachevo diocese; the seminarians